STAT3 Regulates miR-384 Transcription During Th17 Polarization - Han, Jingjing; Liu, Yaping; Zhen, Fei; Yuan, Wen; Zhang, Wei; Song, Xiaotao; Dong, Fuxing; Yao, Ruiqin; Qu, Xuebin (Frontiers in Cell and Developmental Biology, 2019)
MicroRNAs are powerful regulators of gene expression in physiological and pathological conditions. We previously showed that the dysregulation of miR-384 resulted in a T helper cell 17 (Th17) imbalance and contributed to the pathogenesis of experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis. In this study, we evaluated the molecular mechanisms underlying the abnormal increase in miR-384. We did not detect typical CpG islands in the Mir384 promoter. Based on a bioinformatics analysis of the promoter, we identified three conserved transcription factor binding regions (RI, RII, and RIII), two of which (RII and RIII) were cis-regulatory elements. Furthermore, we showed that signal transducer and activator of transcription 3 (STAT3) bound to specific sites in RII and RIII based on chromatin immunoprecipitation, electrophoretic mobility shift assays, and site-specific mutagenesis. During Th17 polarization in vitro, STAT3 activation up-regulated miR-384, while a STAT3 phosphorylation inhibitor decreased miR-384 levels and reduced the percentage of IL-17+ cells, IL-17 secretion, and expression of the Th17 lineage marker Rorγt. Moreover, the simultaneous inhibition of STAT3 and miR-384 could further block Th17 polarization. These results indicate that STAT3, rather than DNA methylation, contributes to the regulation of miR-384 during Th17 polarization.